The enigma of an EBV - Positive mucocutaneous ulcer: A case report and brief review of literature - Nikita J. Mulchandani; Ann Kurian; K. Kalaichelvi; Kannan Subbiah; Annapurneswari Subramanyan (Elsevier, 2022)
Epstein-Barr virus mucocutaneous ulcer (EBVMCU) was first described by Dojcinov et al. in 2010 as a lymphoproliferative disorder presenting with a circumscribed cutaneous or mucosal ulcer in the setting of immunosuppression or immune senescence. Histologically, EBVMCUs show a polymorphous infiltrate of large B-cells with Hodgkin/Reed-Sternberg (HRS) - like cells intermixed with plasmacytoid cells and T cells which may be reminiscent of lymphomas. However, these lesions usually show an indolent disease course followed by spontaneous remission. In this article we present the case of a 33 year old immunocompetent male diagnosed with EBVMCU and also a review of oropharyngeal EBVMCUs.